2012
DOI: 10.1111/j.1574-0862.2012.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Rental markets for cultivated land and agricultural investments in China

Abstract: The purpose of this paper is to empirically track the progress and consequences of the emergence of cultivated land markets in China since 2000. We draw on a set of nationwide, household-level panel data (for 2000 and 2008) and find that the markets for cultivated land rental have emerged robustly. According to our data, 19 of China's cultivated land was rented in farm operators in 2008. We also find that the nature of China's cultivated land rental contracts has become more formal and lengthened the period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 14 publications
(30 reference statements)
0
67
0
2
Order By: Relevance
“…The study by Reda et al [19] indicated that grain yield declined with farmland consolidation. Gao et al [33] found that farmland rental contributed to the falling rates of investment in organic manure, and it might have negative impacts on agricultural productivity. A study on China and India showed a positive relationship between plot size and land yields in China, while a negative relationship between plot size and agricultural productivity in India [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Reda et al [19] indicated that grain yield declined with farmland consolidation. Gao et al [33] found that farmland rental contributed to the falling rates of investment in organic manure, and it might have negative impacts on agricultural productivity. A study on China and India showed a positive relationship between plot size and land yields in China, while a negative relationship between plot size and agricultural productivity in India [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the booming off-farm labor markets have also accelerated the development of farmland rental markets [21][22][23]. China's farmland rental policy gained rapid support, while only 5.2% of contracted farmland was leased in 2007, 33.3% had been leased by the end of 2015 [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes have, of course, affected the nature of farming. As more households began to work full-time off the farm, they also began to rent out their land (Gao et al 2012). Those who stayed are the ones renting this land, which is behind a steady increase in farm size and increasing pressure to mechanise Huang and Ding 2016;Wang et al 2016).…”
Section: Changes In Agricultural Structure and Rural Employmentmentioning
confidence: 99%
“…This may lower the incentive to undertake farming practices that ensure the long-term fertility of the plot. For example, farm level analysis suggests that there is a significant decrease in the use of organic manure when farmers rent in land (Gao et al, 2012). In general, contract duration for farmland is lower than for urban land which is 70 years for residential land, 50 years for industrial land and 40 years for commercial, tourism or recreational land (World Bank and DRC, 2014).…”
mentioning
confidence: 99%